Irregular eating patterns associate with hypomanic symptoms in bipolar disorders. (2nd January 2021) - Buyukkurt, Asli; Bourguignon, Clément; Antinora, Christina; Farquhar, Elisabeth; Gao, Xiaoya; Passarella, Eloise; Sibthorpe, Duncan; Gou, Karine; Saury, Sybille; Beaulieu, Serge; Storch, Kai-Florian; Linnaranta, Outi
ABSTRACT: Objective: We present novel dimensional methods to describe the timing of eating in psychopathology. We focused on the relationship between current mood in bipolar disorder (BD) and the stability of the temporal pattern of daily eating events. Methods: Consenting BD patients ( n = 69) from an outpatient, tertiary care clinic completed hourly charts of mood and eating for two weeks. Mood was also evaluated with Montgomery-Åsberg Depression Rating Scale (MADRS) and Young Mania Rating Scale (YMRS). Results: Illustrative displays, or eatograms, enabling visualization of all recorded eating events were used to guide assessment of the temporal structure of eating across the two week assessment period. We computed indices to quantify irregularities in timing of eating, namely I FRQ, I TIM and I INT for the variability of frequency, timing, and interval of eating events, respectively. In this cohort, irregular temporal pattern of eating correlated with hypomanic symptoms (YMRS with I FRQ, Spearman rank order rh = 0.28, p = .019, with I TIM, rh = 0.44, p < .001, and with I INT rh = 0.38, p = .001), but not depressive symptoms or anthropometric measures. Conclusions : Our data suggest a link between the instability of the temporal order of daily eating and mood. The dimensional measures for eating pattern introduced here enable future investigations of correlations with psychopathology. GRAPHICAL ABSTRACT: